Cdc45-MCM-GINS, a new power player for DNA replication - Aparicio, Tomás (BioMed Central, 2006)
The identity of the DNA helicase(s) involved in eukaryotic DNA replication is still a matter of debate, but the mini-chromosome maintenance (MCM) proteins are the chief candidate. Six conserved MCM proteins, Mcm2–7, are essential for the initiation and elongation stages of DNA replication, contain ATP binding pockets and can form a hexameric structure resembling that of known prokaryotic and viral helicases. However, biochemical proof of their presumed function has remained elusive. Several recent reports confirm that the MCM complex is part of the cellular machine responsible for the unwinding of DNA during S phase. In one of these reports, the helicase activity of Mcm2–7 is finally revealed, when they are purified in association with two partners: initiation factor Cdc45 and a four-subunit complex called GINS. The Cdc45-MCM-GINS complex could constitute the core of a larger macromolecular structure that has been termed the "replisome progression complex".